The Century Dictionary and Cyclopedia with A New Atlas of The World: A Work of Universal Reference in All Departments of Knowledge: Volume V: Hoop. I. J. K. L. - William Dwight Whitney 1827-1894; Benjamin E. Smith (New York The Century co., 1911)
12 volumes : illustrations, maps.
v. 1-8. Dictionary.--v. 9. Cyclopedia of names.--v. 10. Atlas.--v. 11-12. Supplement. [c1906-09]
Prepared under the superintendence of William Dwight Whitney. Revised and Enlarged Edition
Keywords: Encyclopedias (3GdehShYGJs; English language -- Dictionaries; General; Atlases; Biography -- Dictionaries